Methods in psychological research - Evans, Annabel Ness; Rooney, Bryan J. (Los Angeles, California : Sage, 2014)
This interactive and highly applied text engages students with a rich mix of pedagogy (including unique FAQs and FYIs), a casual and accessible writing style and examples of real psychological research from both academic literature and student research projects.
1. Introduction to research in psychology -- 2. Understanding -- 3. Research in psychology : an ethical enterprise -- 4. Hypothesis testing, power, and control : a review of the basics -- 5. Measuring variables -- 6. Selecting research participants -- 7. Experimental design : independent-groups design -- 8. Experimental design : dependent-groups and mixed-groups designs -- 9. Experimental design : single/participants designs/the operant approach -- 10. Nonexperimental research : finding relationships among variables -- 11. Data collection methods -- 12. Program evaluation, archival research, and meta-analytic designs -- 13. Your research project : analyzing, interpreting, and presenting your research -- 14. Communicating in psychology
Includes bibliographical references and index.
Keywords: PSYCHOLOGY--RESEARCH--METHODOLOGY